FILSAFAT RUMAH TANGGA: TELAAH PEMIKIRAN KHAWAJAH NASHIRUDDIN ATH-THUSI - Rakhman, Itmam Aulia (Lembaga Ta'lif wa An-Nasyr (LTN) PBNU, 2018)
Ath-Thusi uses Aristotle's understanding of the practical reason of the theory of surgery. According to Ath-Thusi, the cause of deviation is anything excessive. Thus, the unbalanced state of the soul is caused by the advantages, disadvantages, or morbidity of the mind. Diversity in a society is a necessity, a household, as the smallest community of a complex society and full of differences, it is certainly necessary to be based on the building of togetherness and mutual respect between one another. This article will describe the creative ideas of Khawajah Nashiruddin Ath-Thusi related to the philosophy of the household in order to answer the present-day problematic of the family.